De Novo Acute Myeloid Leukemia with Combined CBFB-MYH11 and BCR-ABL1 Gene Rearrangements: A Case Report and Review of Literature - Sethapati, Venkata Rakesh; Jabr, Ra’ed; Shune, Leyla; El Atrouni, Wissam; Gonzales, Patrick R.; Cui, Wei; Golem, Shivani (Case Reports in Hematology, 2020)
Acute myeloid leukemia (AML) with inv(16)(p13.1q22) resulting in CBFB-MYH11 fusion is associated with a favorable prognosis. The presence of a KIT mutation modifies it to an intermediate prognosis. Additionally, inv(16) can cooperate with other genetic aberrations to further increase cell proliferation. Coexistence of inv(16) and t(9;22) is extremely rare (20 cases). We present a case of a 55-year-old male with elevated white blood cell count. Bone marrow evaluation and flow cytometry analysis were compatible with AML with monocytic features. Cytogenetic studies revealed two-related clones, a minor clone with inv(16) and a major clone with concurrent inv(16) and t(9;22) rearrangements. Fluorescent in situ hybridization studies confirmed these rearrangements. Molecular analysis detected a p190 BCR-ABL1 transcript protein. KIT mutations were negative. The patient was initially treated with standard induction regimen; 7 daily doses of cytarabine from day 1–day 7, 3 daily doses of daunorubicin from day 1–day 3, and 1 dose of Mylotarg (gemtuzumab ozogamicin) on day 1. The detection of t(9;22) led to the addition of daily doses of dasatinib (tyrosine kinase inhibitor) from day 7 onwards. The patient achieved complete remission on day 45. During his treatment course, he acquired disseminated Fusarium infection. Day 180 bone marrow evaluation revealed florid relapse with 64% blasts. Cytogenetic study showed clonal evolution of the inv(16) clone with no evidence of the t(9;22) subclone. Eventually, bone marrow transplantation was contraindicated, and the patient was transferred to palliative care. Literature review revealed that AML with co-occurrence of CBFB-MYH11 and BCR-ABL1 gene rearrangements was involved by only a small number of cases with de novo and therapy-related AML. Most cases were in myeloid blast crisis of chronic myeloid leukemia (CML). Treatment and prognosis among the de novo AML cases varied and majority of them achieved clinical remission. In contrast, these cytogenetic abnormalities in the blast phase of CML had a poor prognosis. As the prognosis and management of AML is dependent upon the underlying genetic characteristics of the neoplasm, it is imperative to include clinical outcome with such rare combinations of genetic alterations.